Cryptonetworks - The incentive-based Economics of Blockchain - Hennessy, Seamus (School of Economics, 2021)
Blockchain technology has the novel ability to ‘create' trust in a decentralised environment. With this technology, third-parties and middlemen are no longer necessary to enforce transactions. Instead, blockchain uses decentralised consensus protocols and embedded logic to enforce contracts. The applications of blockchain are vast and include cryptonetworks, the culmination of blockchain and crypto tokens. Cryptonetworks can have an impact on the business models of firms, both in terms of cost structure and value creation. By blending the functionality of centralised platforms with the community-orientated nature of the original open protocols of the internet, cryptonetworks enable value creation to be correctly assigned to the actual content creators through tokens. The work of Ronald Coase illustrated the need for firms to overcome the transaction costs of operating within the market. Cryptonetworks, however, provide an alternative ‘middle ground' option to the firm and the market, allowing both to benefit from reduced transaction costs and incentive maximisation of the market. In addition, the implementation of economics in today's cryptonetworks, often referred to as ‘cryptoeconomics', remains conventional and conservative, placing a limit on the potential of cryptonetworks. By revaluating and reconstructing today's value measurement criteria, cryptonetworks have the potential to move beyond a single ‘Hayekian price' and instead incorporate multiple other indexes that better measure and capture value creation as it pertains to wider social issues of production, distribution, and consumption of goods and services. Finally, this thesis incorporates a case study on the MakerDAO stablecoin as a practical illustration of a cryptonetwork.